Monolithic crystal filters using lithium tantalate crystal - MATEESCU, I.; GACKOWSKA, G.; KORONY, G.; BORA, C. (Archives of Acoustics, 1991)
The characteristics of lithium tantalate crystal filters and the method of their design are described. The experimental results are presented and discussed.